Implikatur Non-Konvensional pada Novel 5 Cm Karya Dony Dirgantara: Implikatur Non-Konvensional pada Novel 5 Cm Karya Dony Dirgantara - Windo Dicky Irawan (Universitas Muhammadiyah Kotabumi, 2020)
This research on non-conventional Implications is based on the 5 cm Novel by Donny Dirgantara. A literary work can be researched, enjoyed, and lived in, as well as studies related to real-life images used by the author. Readers can look for implicit meanings, or something different from what the speaker actually says. Therefore, the aim of this study is to look at the conversations of the characters in Donny Dhirgantoro's 5cm novel non-conventional. The method used in this research is descriptive method through a qualitative approach. Based on the results of the research, there are twelve non-conventional data that have the meaning of meaning, namely wanting to imply something with the truth.